Study of TSH level at the time of diagnosis of Hypothyroidism in patients with Diabetes Mellitus- A Retrospective Study - K.C., Indu; Ghimire, S; Deo, R (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Background: To evaluate the difference in the level of TSH in diabetic and non diabetic patients at the time of the diagnosis of hypothyroidism.Methods: 100 diagnosed cases of hypothyroidism, 50 with diabetes and 50 without diabetes were studied. The level of TSH at the time of diagnosis and other information were obtained from the medical records.Results: The mean TSH in patients with the history of diabetes at the diagnosis of hypothyroidism was 19.9616±26.990 and in those without the history of the diabetes was 10.4797±6.503 (p value 0.018). The females with diabetes had higher level of TSH level at the time of diagnosis of hypothyroidism than females without diabetes (p value 0.045). There was no statistically significant difference in the level of TSH in males with and without diabetes at the time of diagnosis of hypothyroidism.Conclusion: Patients with diabetes mellitus had higher level of TSH at the time of diagnosis of hypothyroidism in comparison to those without diabetes. Early identification of the raised TSH levels in diabetic patients and timely intervention will help to reduce the chances of adverse cardiovascular outcomes and diabetic kidney disease in this group of patients.